2010
DOI: 10.1111/j.1468-2850.2009.01197.x
|View full text |Cite
|
Sign up to set email alerts
|

Allegiance or fidelity? A clarifying reply.

Abstract: [Clin Psychol Sci Prac 17: 82–89, 2010] Recently, in the journal Clinical Psychology: Science and Practice, there appeared a systematic review (Blair, Marcus, & Boccaccini, 2008) accompanied by a commentary (Lilienfeld & Jones, 2008) suggesting an “allegiance effect” in the reporting of the predictive accuracy of actuarial risk assessment systems. The authors of these two articles suggested some possible errors or misrepresentation on the part of original developers or other researchers and proposed some reme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 68 publications
3
27
0
Order By: Relevance
“…We note that other risk scales developed in Canada also do well in Canada (e.g., Harris et al, 2009;Olver et al, 2009;Yang et al, 2010). We believe this is in large part attributable to the fact that Canadian researchers bring integrity, first, to the administration of their own instruments (predictor variable) by maximizing measurement precision and, second, to the determination of offender recidivism (outcome variable) by consistently using a comprehensive, national database.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We note that other risk scales developed in Canada also do well in Canada (e.g., Harris et al, 2009;Olver et al, 2009;Yang et al, 2010). We believe this is in large part attributable to the fact that Canadian researchers bring integrity, first, to the administration of their own instruments (predictor variable) by maximizing measurement precision and, second, to the determination of offender recidivism (outcome variable) by consistently using a comprehensive, national database.…”
Section: Discussionmentioning
confidence: 91%
“…As noted previously, enhanced quality of assessments of the criterion will allow the magnitude of predictive validity estimates to approach their asymptote no matter the instrument under investigation. Similarly, Harris et al (2009) demonstrated fidelity in their review of VRAG validity research in that the quality of the VRAG assessment and the criterion outcome measure accounted for the effect of author involvement.…”
Section: Two Considerations: Gender and Nationalitymentioning
confidence: 95%
“…Previous work has proposed several possible explanations of such bias [7], [9], [45]. First, tool designers may conduct studies to maximize the predictive validity of their instruments.…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analytic evidence concerning the existence of an authorship effect in the risk assessment literature is limited and reports contrasting conclusions [7][9]. First, Blair and colleagues [7] explored an authorship effect using the literature on the Violence Risk Appraisal Guide (VRAG) [10], [11], the Sex Offender Risk Appraisal Guide (SORAG) [10], [11], and the Static-99 [12], [13]–actuarial risk assessment tools designed for use with adult offenders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation